Analysis of Muhammadiyah Political Texts and Networks in the Indonesian Context of Governance and Local Politics - Hardinda, Hardinda; Razak, Muhammad Rais Rahmat; Lawelai, Herman (Universitas Pancasakti, 2025)
This study analyzes Muhammadiyah's political texts and networks within the context of Indonesian governance and local politics using a literature review and text analysis. Data were sourced from the Scopus database, comprising 77 documents from 1995 to 2024, analyzed using the Prisma method, and visualized through InfraNodus. The findings reveal Muhammadiyah's significant role in various political aspects, including political Islam, intellectual thought, and election dynamics. Network analysis and word cloud visualizations uncover complex relationships between key concepts, highlighting Muhammadiyah's influence in shaping political discourse and Muslim identity in Indonesia. Practical implications include developing more effective and inclusive policies involving Muhammadiyah. Research limitations include data and analysis method constraints, while suggestions for future research involve incorporating additional data sources and mixed methods for deeper insights.